Columbianadin Dampens In Vitro Inflammatory Actions and Inhibits Liver Injury via Inhibition of NF-κB/MAPKs: Impacts on ∙OH Radicals and HO-1 Expression - Thanasekaran Jayakumar; Shaw-Min Hou; Chao-Chien Chang; Tsorng-Harn Fong; Chih-Wei Hsia; Yen-Jen Chen; Wei-Chieh Huang; Periyakali Saravanabhavan; Manjunath Manubolu; Joen-Rong Sheu; Chih-Hsuan Hsia (MDPI AG, 2021)
Columbianadin (CBN), a natural coumarin isolated from Angelica decursiva, is reported to have numerous biological activities, including anticancer and platelet aggregation inhibiting properties. Here, we investigated CBN's anti-inflammatory effect in lipopolysaccharide (LPS)-stimulated RAW 264.7 cell activation and deciphered the signaling process, which could be targeted by CBN as part of the mechanisms. Using a mouse model of LPS-induced acute liver inflammation, the CBN effects were examined by distinct histologic methods using trichrome, reticulin, and Weigert's resorcin fuchsin staining. The result showed that CBN decreased LPS-induced expressions of TNF-α, IL-1β, and iNOS and NO production in RAW 264.7 cells and mouse liver. CBN inhibited LPS-induced ERK and JNK phosphorylation, increased IκBα levels, and inhibited NF-κB p65 phosphorylation and its nuclear translocation. Application of inhibitors for ERK (PD98059) and JNK (SP600125) abolished the LPS-induced effect on NF-κB p65 phosphorylation, which indicated that ERK and JNK signaling pathways were involved in CBN-mediated inhibition of NF-κB activation. Treatment with CBN decreased hydroxyl radical (•OH) generation and increased HO-1 expression in RAW 264.7 cells. Furthermore, LPS-induced liver injury, as indicated by elevated serum levels of liver marker enzymes (aspartate aminotransferase (AST) and alanine aminotransferase (ALT)) and histopathological alterations, were reversed by CBN. This work demonstrates the utility of CBN against LPS-induced inflammation, liver injury, and oxidative stress by targeting JNK/ERK and NF-κB signaling pathways.